Religious Activities for Muslim Elderly at the Senior Citizens Activity Center (PAWE) in Pahang, Malaysia - Siti Marsitah, Mohd Mokhtar; Norazmi, Anas; Norhapizah, Mohd Burhan; Rashidi, Abbas; Hasiah, Mat Salleh; Anaztasia Natasha, Muhamad Ramlan (Human Resource Management Academic Research Society (HRMARS), 2022)
Religious activity is one of the pursuits favoured by the Muslim elderly at Senior Citizens Activity Center (PAWE) in their attempts to expand knowledge and comprehension related to the fundamentals of religion as well as to strengthen Islamic character within; these are essential to produce elderly who are healthy, with integrity, secured and dignified, consistent with the requirements in Islam. Hence, this study is dedicated to analyzing religious activities and challenges faced by Muslim elderly at the Senior Citizens Activity Center (PAWE) in Pahang. The qualitative study design by means of a case study using a semi-structured interview instrument involving officers/administrators of the Senior Citizens Activity Center (PAWE) was conducted all over Pahang to examine the religious activities and issues faced by Muslim elderly at other PAWE branches. 7 PAWE officers/administrators from 7 different districts in Pahang, namely Bera, Cameron Highland, Jengka, Maran, Muadzam, Raub and Temerloh districts were selected for purposive sampling. ATLAS ti9 software-assisted content analysis was utilized to assess the interview findings. The study’s outcome revealed that the religious activities organized by PAWE are favoured by Muslim elderly participants, videlicet (i) Recitation classes (iqra', al-Qur’an & tajwid), (ii) Talks/ Daily tazkirah/weekly/monthly/, (iii) Lessons for religious studies (fardhu ain & tasawuf) and marhaban classes. Nevertheless, there are slight concerns over these elderly’s abilities in partaking the religious activities about problems related to their vision and hearing, poor recitation of the Qur'an as well as transportation, especially those living in rural areas. The organization of iqra' recitation classes and transportation arrangement by PAWE are highly effective in enhancing the number of elderly’s involvement in religious activities administered by PAWE in Pahang. Hence, further research is proposed on model development or a new holistic, comprehensive, and consistent religious module that can be developed by PAWE management with support from the Senior Citizens Division (BWE), under Social Welfare Department (JKM) at the state and federal levels, to be utilized by all PAWEs in our country.